ANALISIS RISIKO DAN MANFAAT PENGGUNAAN MORFIN: TINGKAT PEMAHAMAN MAHASISWA SEBELUM DAN SESUDAH PENYULUHAN - Adriany, Rina; Rahmawati, Dewi; Akbar, Rayhan; Agustina, Monica; Budipratama Adina, Anugerah (Universitas Mataram, 2025)
Morphine abuse as an opioid is a global public health issue due to its high-risk yet effective use as a potent analgesic. A lack of understanding about morphine can increase the potential for misuse, especially among non-health students who are often not exposed to in-depth information about its risks and benefits. Therefore, counseling on morphine is necessary to improve awareness about this drug. This community service activity aimed to increase the understanding of non-health students about morphine, focusing on its risks and benefits. The activity was conducted through interactive counseling for 20 students from the Department of Informatics Engineering at Universitas Global Jakarta, utilizing educational posters as the medium of instruction. Evaluation was performed using pre-tests and post-tests to measure participants' understanding before and after the counseling. The pre-test results showed a low initial understanding of only 37.5%. After counseling, there was a significant improvement in the students' learning, with the post-test results reaching 95%. These results demonstrate that communicative and visual educational methods are effective in bridging the knowledge gap among students from different disciplines. Counseling on morphine not only enhanced understanding of its risks and benefits but also enriched chemical literacy and public health awareness. Such education is essential for raising awareness among students about the potential risks of drug abuse. In the future, this type of counseling should be expanded to other study programs and further enhanced with more profound knowledge of health policies related to the use of high-risk drugs.